Perawatan saluran akar vital molar kedua kiri mandibula dengan restorasi fiber post, core dan mahkota zirkonia - Stefani, Rosita; Subrata, Aryadi; Ratnasari, Dina; Claudiary Sinatra, Talisa; Barbie Lim, Maria; Kenneth Kurniawan, Alexander; Tjingson, Natalia (Fakultas Kedokteran Gigi Universitas Trisakti, 2025)
Background: Endodontically treated teeth are prone to biomechanical failure due to substantial structural loss, often necessitating fiber post–core and Zirconia crown restorations to re-establish tooth integrity and function. The choice of fiber post–core and Zirconia crown is determined by the amount of remaining tooth structure. Case Description: A 38-year-old male presented with a two-month history of throbbing pain in tooth 37, accompanied by discomfort during mastication. The patient had been self-medicating with mefenamic acid and reported no systemic illnesses. Intraoral examination revealed moderate oral hygiene (OHI-S 2) and a large occlusal cavity with a pulp polyp (Black Class II, Mount–Hume 2.4, ICDAS D6). Cold testing elicited a positive response, with tenderness to percussion but normal mobility and probing depths. Radiographic evaluation demonstrated pulp chamber radiolucency, widening of the periodontal ligament space, thickening of the lamina dura, and periapical radiolucency. The diagnosis was symptomatic irreversible pulpitis with apical periodontitis. The patient underwent root canal therapy followed by post–core and crown restoration. Discussion: Fiber-reinforced composite (FRC) posts provide dentin-like elasticity, favorable esthetics, and superior fracture resistance compared to metal posts, allowing more uniform stress distribution in endodontically treated teeth. The use of an FRC post combined with a Zirconia crown following root canal therapy successfully restored the tooth’s structure, function, esthetics, and long-term retrievability. Conclusion: Fiber post–core and Zirconia crown restoration is an effective approach for rehabilitating endodontically treated teeth at risk of biomechanical failure, offering dentin-like elastic properties and uniform stress distribution to optimize functional and esthetic outcomes.